Field measurement of microclimate of sunken square and its effect on indoor environment of underground metro station in subtropical region. (15th January 2023) - Zhao, Jianjian; Dong, Jiankai; Zhang, Xiaohai; Na, Yanling; Jiang, Chongxu; He, Feng; Cui, Qijie; Liu, Jing
Abstract: Because of the needs of rail transit and urban construction, metro stations have various forms of entrances. In particular, in recent years, the sunken square has been increasingly designed and applied to underground transportation hub systems. Because the sunken square is directly connected to the indoor environment through the entrances, the microclimate of the sunken square can directly affect the indoor environment. When air enters the underground transportation hub through the entrance, it has a nonnegligible impact on indoor thermal comfort and energy consumption. In this study, two representative metro stations with sunken squares in Shenzhen, China, which is a typical metropolis in a subtropical region, were selected. The microclimates of the sunken squares were investigated, the air flow rates through the entrances were measured, and the indoor environments of the two stations were studied. The test results show that the attenuation effect of wind increases with the shape coefficient of the sunken squares. In addition, the temperature gradually increases from the bottom to the top of the sunken square. The neutral physiological equivalent temperature (PET) in the sunken squares was 29 and 19 °C in summer and winter, respectively. Meanwhile, the air flow rate through the sunken square entrances was relatively large, and the influence factor was obtained. The results of the systematic measurements provide a data basis and technical guidance for the design of sunken squares and metro stations, and can help improve the quality of the indoor environment in such underground metro stations. Highlights: The microclimates of the sunken squares were investigated, the air flow rates through the entrances were measured. The indoor environments of the two underground metro stations were studied. The attenuation effect of wind increases with the shape coefficient of the sunken squares. The neutral physiological equivalent temperature (PET) in the sunken squares was obtained in summer and winter, respectively. The air flow rate through the sunken square entrances was relatively large, and the influence factor was obtained.